Kegiatan Pembelajaran Berbasis Islam di PAUD - Achmad Ruslan Afendi; Rahmat Hamdani; Harisa US; Paujiah Paujiah; Pradhita Mahdayani; Salamah Salamah (Program Pascasarjana Universitas Pesantren Tinggi Darul Ulum (Unipdu) Jombang, 2022)
This study aims to describe learning activities in Islamic-based Early Childhood Education (PAUD) institutions and the obstacles that occur in the process of implementing them. This research was conducted at the PAUD Rasyiqah Samarinda Seberang East Kalimantan. This research uses qualitative research methods with a descriptive approach. Data collection techniques used in this study were observation, interviews, and documentation. The results of the research conducted at PAUD Rasyiqah Samarinda Seberang East Kalimantan showed that the vision of an Islamic-based institution was in sync with the learning activities carried out in the classroom. This is shown by activities that shape the character of salih and saliha children’s manners, saving and infaq every day, cleanliness and tidiness, iqrar or praying before and after studying, reciting al-asma’ al-husna, Duha prayer activities, recitation of the Qur’an using the Qiroati method which is the flagship program, reading daily prayers and the Qur’an, as well as reading selected hadiths. These activities are carried out every day summarized in the 9 (nine) pillars of salih/saliha children as an effort to realize the vision of the institution. Meanwhile, the obstacle faced by the institution is the teacher’s recruitment, if there is one teacher who is licensed, then learning is not optimal, coupled with the presence of children with special needs, so they need a shadow teacher for the child with special needs.